The Tradition of Constructivism - Bann, Stephen (London : Thames and Hudson, 1974)
Contents: I. Constructivism in Russia: 1920-23 ; II. Toward International Constructivism: 1921-22 ; III. Constructivism and the Little Magazines: 1923-24 ; IV. Extension of Constructivist Principles: 1923-28 ; V. Retrospect, Theory, and Prognosis: 1928-32 ; VI. The Constructive Idea in Europe: 1930-42 ; VII. The Constructive Idea in the Postwar World: 1923-24
Lissitzky, El ; Gabo, Naum ; Tatlin, Vladimir ; van Doesburg, Theo ; etc.
Engels
boek